Nasal Valve Lift in Nasal Valve Stenosis—A 2 Years Clinical Trial - Heppt, Helen; Vent, Julia; Alali, Mohammad; Paal, Caroline; Heppt, Werner (Facial Plastic Surgery, 2019)
A clinical study was conducted to determine the effect of nasal valve lift treatment using absorbable, polylactic acid, self-retaining cone threads (Silhouette Soft) in patients with nasal valve stenosis. Sixty patients (n = 60) were included in this prospective study which was performed from January 2015 until December 2018, 19 patients dropped out due to noncompliance. Initially, participants were divided into two equal groups. One was treated by nasal valve lift only, the other additionally received turbinoplasty. A visual analog scale (VAS) was used to rate the sense of nasal ventilation. Patients' satisfaction was examined by a categorical scale, preoperatively, after 1 week, and after 1, 6, 12, 18, and 24 months. For statistical analysis, an univariant variance analysis was conducted to test the significance of differences in nasal breathing within one group at different points of postoperative controls, with the statistical significance set at p < 0.05. Moreover, the two groups were compared with each other regarding results of the categorical scale. After surgical treatment, an improvement is reported by all participants. Average VAS scores were significantly lower between preoperative and every postoperative rating. Although a decline in the effect of breathing improvement is recognizable as threads are dissolved, patients' satisfaction in improvement of nasal breathing is persistent in most cases, even at long-term observation. Overall, these results demonstrate that valve lift is an effective method to treat patients with nasal valve stenosis.
Keywords: nasal valve stenosis; nasal valve lift; absorbable coiled PLA threads; nose surgery; rhinoplasty